d-Glucuronate and d-Glucuronate Glycal Acceptors for the Scalable Synthesis of d-GlcN-α-1,4-d-GlcA Disaccharides and Modular Assembly of Heparan Sulfate - Pongener, Imlirenla; Miller, Gavin J. J. (Journal of organic chemistry, 2023)
Reported herein is a scalable chemical synthesis of disaccharidebuilding blocks for heparan sulfate (HS) oligosaccharide assembly.The use of d-glucuronate-based acceptors for dehydrativeglycosylation with d-glucosamine partners is explored, enablingdiastereoselective synthesis of appropriately protected HS disaccharidebuilding blocks (d-GlcN-& alpha;-1,4-d-GlcA) on amultigram scale. Isolation and characterization of key donor (1,2glycal)- and acceptor (ortho-ester, anhydro)-derived side productsensure methodology improvements to reduce their formation; protectingthe d-glucuronate acceptor at the anomeric position witha para-methoxyphenyl unit proves optimal. We alsointroduce glycal uronate acceptors, showing them to be comparativein reactivity to their pyranuronate counterparts. Taken together,this gram-scale access offers the capability to explore the iterativeassembly of defined HS sequences containing the d-GlcN-& alpha;-1,4-d-GlcA repeat, highlighted by completing this for two tetrasaccharidesyntheses.